MATRIX METHOD IN TASKS OF SEISMOLOGY - Malytskyi, D.; Muyla, O.; Pavlova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The solution of the direct problem for the displacement field on the free surface of layered isotropic medium using the matrix method is presented. The results of the direct problem are used to determine the seismic moment tensor. The application of the method of matrix propagator for the anisotropic medium is shown.